Women’s Representation in Political Institutions - Sílvia Claveria (Revista d'Estudis Autonòmics i Federals, 2022)
This article examines the presence of women in Catalan political institutions from 1980 until now. First, this report reviews the measures that have been adopted over the years to reduce male over-representation. Second, it presents women’s political representation in Catalonia, with a special emphasis on the Parliament, the Government, and local authorities. It also analyses the factors that account for this gender gap. Third, it exposes the measures that have been implemented in other places — such as Spain’s autonomous communities, European countries, or Latin American countries — to boost women’s representation. Finally, this paper suggests measures that can be implemented to improve or maintain the representation of women in Catalan institutions. This study focuses on Catalonia since it allows the analysis of the presence of women in sub-state institutions.